PENGARUH PEMBELAJARAN MATEMATIKA REALISTIK TERHADAP KEMAMPUAN OPERASI HITUNG PENJUMLAHAN PADA SISWA TUNAGRAHITA - Raedix Desta Kusuma; Abdul Huda (Universitas Negeri Malang, 2014)
This research aims to (1) describe the results of student learning arithmetic summation before applied learning mathematics realistic, (2) describe the learning outcomes of students after applied arithmetic summation learning mathematics realistic, (3) the effect of application of learning mathematics realistic summing arithmatics operation in children with intelectual and development disabilities at Special Education School Class II. This study uses a quantitative approach, with a pre-experimental design, and a one-group pretest-posttest design. Research sample are children with intelectual and development disabilities class II, amounting to 10 people. Collecting data using achievement test. Analysis of data using test formula sign (sign test). The conclusion of this study is that there is a significant effect of application of learning mathematics realistic summing arithmetic operation capability for intelectual and development disabilities students class II. Penelitian ini bertujuan (1) mendeskripsikan hasil belajar berhitung penjumlahan siswa sebelum diterapkan pembelajaran matematika realistik, (2) mendeskripsikan hasil belajar berhitung penjumlahan siswa sesudah diterapkan pembelajaran matematika realistik, (3) pengaruh implementasi pembelajaran matematika realistik terhadap kemampuan operasi hitung penjumlahan siswa tunagrahita. Penelitian ini menggunakan pendekatan kuantitatif, dengan jenis penelitian pre-eksperimental, dan one-group pretest-posttest design. Sampel penelitiannya adalah siswa tunagrahita kelas II yang berjumlah 10 orang. Pengumpulan data menggunakan tes hasil belajar. Analisis data menggunakan rumus uji tanda (sign test). Kesimpulan penelitian ini adalah terdapat pengaruh signifikan penggunaan pembelajaran matematika realistik terhadap kemampuan operasi hitung penjumlahan siswa tunagrahita kelas II.